2022
DOI: 10.1177/07410883221083517
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and Embodiment in Multimodal Meaning Making

Abstract: Immersive virtual reality (VR) technology is becoming widespread in education, yet research of VR technologies for students’ multimodal communication is an emerging area of research in writing and literacies scholarship. Likewise, the significance of new ways of embodied meaning making in VR environments is undertheorized—a gap that requires attention given the potential for broadened use of the sensorium in multimodal language and literacy learning. This classroom research investigated multimodal composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Moreover, multimodal integration has also been investigated in the field of embodied cognition. Studies showed that individuals use their body and their senses as different sources of information and that they integrate them to communicate more effectively ( Price and Jewitt, 2013 ; Mills et al, 2022 ). However, no study has investigated the integration of bodily resonances in the perception of emotional prosody in a multimodal context.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multimodal integration has also been investigated in the field of embodied cognition. Studies showed that individuals use their body and their senses as different sources of information and that they integrate them to communicate more effectively ( Price and Jewitt, 2013 ; Mills et al, 2022 ). However, no study has investigated the integration of bodily resonances in the perception of emotional prosody in a multimodal context.…”
Section: Introductionmentioning
confidence: 99%
“…VR technologies offer different affordances for embodied writing and multimodal communication, distinguished from previous forms of virtual technology with the advent of HMDs that have become prominent since 2013 (Jensen & Konradsen, 2018). These affordances account for multimodal and sensorial ways of interacting with sophisticated, three-dimensional virtual environments and objects, orchestrating vision, sound, haptics (touch to interact with the environment), and head and body movements, in fully immersive environments [4].…”
Section: The Embodiment Of Multimodal Concept In Virtual Reality Devicesmentioning
confidence: 99%
“…For example, the floor texture of the exhibition hall is depicted by maps [16] . The mapping of the model generally requires UV unwrapping through Maya, and then the mapping is completed in Photoshop [17] . In order to improve the system performance, it is necessary to minimize the number and amount of maps.…”
Section: Mapping Of Basic Model Librarymentioning
confidence: 99%